Bahasa Inggris Bahasa Inggris - Dwi Putra, Maulana Yogi Aditya; Kriswibowo, Arimurti (Faculty of Social Science, Universitas Negeri Padang, 2024)
Digitalization is an innovation based on technological advances that can make governance more effective and efficient. This makes human activities carry out digital transformation in both the public and private sectors. One of the implementations of digital transformation in the public sector is the implementation of Digital ID cards. Digital transformation in the context of digital ID cards must be balanced with the readiness of both implementers and the community as policy actors. This research identifies digital transformation in the context of Digital KTP in Surabaya City using the imperative strategy theory of digital transformation model Verhoef which has 4 indicators, namely: Digital Resources, Organizational Structure, Improvement Strategy, and Measures and Goals. Data is obtained through analysis of observation results, documentation, and interviews with implementing agencies and the community. The results of the study found that there was a 25% target non-achievement from the Ministry of Home Affairs of the Republic of Indonesia for the activation of Digital KTP in Surabaya, this was due to a less massive improvement strategy and a lack of public awareness regarding this innovation. This study concludes that there are still indicators that have obstacles such as digital resources, which in its implementation there are still obstacles in the IKD application and growth strategies that still need strategies to reach the elderly and add features to increase the value of innovation to increase public awareness of digital transformation.